A Study of Fuzzy Logic as a Decision Support System for Determining the Best Athletes - Karo-Karo, Siddik; ., .; ., .; ., .; ., . (International Journal of Engineering and Technology, 2018)
The selection of athletes with the best conditions is very required to follow various sports agenda that will be followed, to do the selection can be used decision support system by applying fuzzy logic as a tool of decision maker by doing the selection of variables used. Expected results with the use of this fuzzy logic obtained optimal selection with sufficient variables complete and the best athlete is a recommendation given and not made the final decision.Â Â